Rede de interações entre aves frugívoras e plantas em áreas de floresta estacional decidual, RS - Fontanari, Verônica Azzolin (2018)
Frugivory and seed dispersal are examples of mutualisms, configuring a vital process for plant populations which have their reproductive cycle linked to zoochory dispersal. The set of interactions between these organisms creates a complex network and the understanding how it is structured reveals mechanisms that shape these interactions in nature. The aim of this study was to investigate the network structural pattern of the interactions between frugivorous birds and plants in the municipality of Silveira Martins, Rio Grande do Sul. Three transects were run, in areas of Deciduous Seasonal Forest, totalizing 9.1 km and 540 hours of observations. Traditional network metrics were analyzed to networks study such as Importance and Connectance Indexes, degree distribution, nestedness, modularity and robustness. The mutualistic network observed consisted of 86 species, responsible for 201 interactions. The Connectance Index was C = 0.10. Birds and plants generalists made up the dense nucleous of the network of interactions, presenting the highest values of k. Among them, we can highlight Tachyphonus coronatus (k = 14), Turdus amaurochalinus (k = 13), Turdus rufiventris (k = 13) and Turdus albicollis (k = 12), which also presented the highest Importance Indices. Among the plant species are Cabralea canjerana (k = 21) and Ficus luschnathiana (k = 20). The degree distribution was explained mainly by truncated power law and exponential model, which suggest extremes, where some species preferably connect to already well connected nodes, while the others make random connections. The nested pattern allows to infer that the presence of generalist species forms a dense nucleus of interactions where remaining community is connected, and also demonstrates a greater network resistance to random species extinctions. The lack of modularity indicates the lack of interactions specificity between the species in the network. The robustness index suggests that the network is more resistant to random extinctions than to selective extinctions (from highest to lowest degree). The understanding of how the mutualistc network is structured in areas of Deciduous Seasonal Forest and which its fragilities assist in the management and actions of restoration of natural areas.